Results obtained after the surgical treatment of Graves’ disease depending on the levels of anti-thyroid antibodies - Shliakhtych, S. L.; Antoniv, V. R. (General Surgery, 2021)
Graves’ disease (GD) is a hereditary autoimmune disease which is characterized by persistent abnormal hypersecretion of thyroid hormones and thyrotoxicosis syndrome development. GD affects from 0.5 % to 2.0 % of population in different regions. 46 % of these patients develop ophthalmopathy. GD is a common cause of disabilities in patients under 60 years of age. In recent years, the incidence of GD in Ukraine has increased by 9.9 % — from 106.2 to 117.9 per 100,000 individuals. This can be connected with the improved diagnostic possibilities and active disease detection as well as with the increased number of autoimmune thyroid disorders. The recent studies focus on prevention of specific complications and recurrences of GD after surgery. Objective — to compare the levels of antibodies to the thyroid‑stimulating hormone receptors (TSHR‑Ab) during different postoperative periods as well as the incidence of early and late complications depending on the surgical technique used for the treatment of GD. Materials and methods. The results of surgical treatment of 130 patients, with GD were compared. 29 male patients and 101 female patients aged from 19 to 76 (average — 44.1 ± 3.2 years), receiving their treatment for GD in Kyiv Center of Endocrine Surgery during 2010—2018, were randomly selected and divided into two groups. At the time of operation the duration of disease was from 1 to 30 years (average — 4.6 ± 1.2 years). Group 1 included 65 patients that underwent total thyreoidectomy (TT) and group 2 included 65 patients that underwent subtotal thyreoidectomy (ST). The following parameters were compared: surgery duration, the incidence of early postoperative complications, including bleedings and damage to the recurrent laryngeal nerves, and late outcomes of surgical treatment (persistent hypoparathyreoidism disorder and disorder recurrences) depending on the method of surgery (ST or TT). Furthermore, the patterns of the TSHR‑Ab level reduction were studied for different postoperative periods. Results. The comparison of surgical outcomes following TТ and ST didn’t reveal any statistically significant differences in such evaluation criteria as the average surgery duration, the average volume of intraoperative blood loss and the average duration of the postoperative inpatient treatment. The comparative assessment of the thyroid stump volume and the average amount of drained discharge showed statistically significant differences for TТ. It allows considering TТ as a surgery which causes less complications than ST. The studied parameters of early postoperative complications had no significant differences for ST and TТ. The long‑term (5 years) postoperative level of TSHR‑Ab was statistically significantly lower in patients after TT and made up 1.15 ± 0.13 IU/L (thus corresponding to the normal level). Conclusions. Total thyroidectomy is an optimal surgical technique and is more appropriate compared with subtotal thyroid gland resection. It should be noted that TT provides lower risk of complications due to significantly lower level of TSHR‑Ab in late postoperative period.